Bone morphogenetic protein 6 affects cell-cell communication by altering the expression of Connexin43 in human granulosa-lutein cells. (1st December 2019) - Wu, Hai-Cui; Chang, Hsun-Ming; Yi, Yuyin; Sun, Zhen-Gao; Lin, Yung-Ming; Lian, Fang; Leung, Peter C.K.
Abstract: Connexin 43 (Cx43)-coupled gap junctions in granulosa cells play an important role in follicular development, oocyte maturation, and corpus luteum maintenance. Bone morphogenetic protein 6 (BMP6) is highly expressed in human oocytes and granulosa cells and is involved in the regulation of female reproduction. Currently, whether oocyte- and granulosa cell-derived BMP6 affects the expression of Cx43 and its related gap junction intercellular communication (GJIC) activity in human granulosa cells remains unknown. In this study, we demonstrate that BMP6 treatment significantly suppressed the expression of Cx43 in both primary and immortalized (SVOG) human granulosa-lutein cells. Using both pharmacological inhibitors and small interfering RNA-mediated knockdown approaches, we demonstrate that ALK2 and ALK3 BMP type I receptors are involved in BMP6-induced suppressive effects on Cx43 expression and GJIC activity in SVOG cells. Furthermore, these cellular activities are most likely mediated by the SMAD1/SMAD5-SMAD4-dependent signaling pathway. Notably, the ChIP analyses demonstrated that phosphorylated SMADs could bind to human Cx43 promoter. Our findings provide new insight into the molecular mechanisms by which an intrafollicular growth factor regulates cell-cell communication in human granulosa cells. Highlights: BMP6 downregulates Cx43 expression in human granulosa-lutein cells. DMH-1 and DM reversed BMP6-induced phosphorylation of SMAD1/5/8 and downregulation of Cx43. ALK2 and ALK3 mediate BMP6-induced downregulation of Cx43 and decrease in GJIC activity. SMAD1/SMAD5-SMAD4 signaling is required for BMP6-induced downregulation of Cx43. Phosphorylated SMADs bind to human GJA1(Cx43) promoter in SVOG cells.